Model of the Importance of Socio-Cultural in Waste Management on Penyengat Island - Zainul Ikhwan; R. Hamdani Harahap; Lita Sri Andayani; Miswar Budi Mulya (Lakhomi Journal Scientific Journal of Culture, 2021)
The main problem of waste management in Penyengat Island is the increasing population growth and increasing volume of waste and limited land so that it is difficult to carry out waste management using the final waste treatment site because it has a large potential for pollution. The low level of public awareness in managing household waste is caused by the community's social, economic, and cultural conditions. This study designs Model of the Importance of Socio-Cultural in Waste Management on Penyengat Island. This research method is an analytical survey with a cross-sectional design, the community subjects who live in Penyengat Island with a sample size of 270 people, taken by random sampling. Data analysis using chi-square test and logistic regression. Logical regression equation model in (p/(1-p)) - 1,614 + 0,505 (place of residence) + 0.642 (local wisdom). Waste management needs cultural values that already exist and should be maintained as part of one's identity and efforts to maintain the balance of nature and the environment. It is also necessary to conduct a policy study regarding the island's waste management program with a socio-cultural value approach.